Analisis Kepemimpinan Transformasional Terhadap Motivasi Kerja Di Era Digital Pada Pegawai Biro Organisasi Dan Sdm Kementrian Perdagangan Ri Jakarta Pusat - Wiranti Wiranti; Widowati Widowati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The impact of on employee work motivation at the Biro Organisasi dan Sumber Daya Manusia Kementerian Perdagangan Republik Indonesia, Jakarta Pusat, especially in facing the dynamics of the digital era. This qualitative study utilized in-depth interview techniques with 10 key informants out of a total of 75 employees, supplemented by data triangulation and SWOT analysis to validate the findings. The results revealed that the transformational leadership approach which includes four main dimensions: idealized influence (pengaruh ideal), inspirational motivation (motivasi inspiratif), intellectual stimulation (stimulasi intelektual), and individualized consideration (perhatian individual) as described by Bass in Armansyah (2022:4), successfully strengthened adaptation to digital technology, encouraged innovation, and enhanced intrinsic motivation among employees amid challenges of e-government implementation and government bureaucracy reform. Furthermore, employees who feel motivated to achieve work goals tend to be more satisfied with their jobs. Conversely, employees who feel dissatisfied with their work, whether due to external or internal factors, tend to experience decreased motivation (S. Sutoro, Moh 2024). The study found that transformational leaders create a collaborative work ecosystem by integrating technological tools such as virtual platforms and cloud systems, inspiring subordinates to exceed their personal targets. This effectively reduces resistance to change, decreases work fatigue, and significantly increases overall productivity. The main contribution of this study lies in enriching human resource development in central government agencies, accompanied by strategic recommendations in the form of digital-transformational leadership training programs to strengthen the vision and mission of the organization going forward.